Analysis of Finite Source Queueing System with Catastrophe - Indhumathi, J; Subramanian, A. Muthu Ganapathi; Sekar, Gopal (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we are analyzing the finite source queueing system with catastrophe. This model is completely solved by using continued fraction method. We have calculated the compact solutions of steady state probabilities of number of occupants in the system and various system performance measures. Analytical and pictorial studies are also carried out